2011
DOI: 10.1159/000324647
|View full text |Cite
|
Sign up to set email alerts
|

Bone Cell Autophagy Is Regulated by Environmental Factors

Abstract: The goal of this investigation was to ascertain whether bone cells undergo autophagy and to determine if this process is regulated by environmental factors. We showed that osteocytes in both murine and human cortical bone display a punctuate distribution of microtubule-associated protein light chain 3, indicative of autophagy. In addition, we noted a basal level of autophagy in preosteocyte-like murine long bone-derived osteocytic (MLO)-A5 cells. Autophagy was upregulated following nutrient deprivation and hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 13 publications
4
52
0
2
Order By: Relevance
“…However, particulate LC3 fluorescence has not been observed in bone-lining cells or osteoblasts. Furthermore, autophagic osteocytes were primarily observed residing at a distance from the haversian canal2324. Our study found the expression of LC3 in osteoblasts which indicated that osteoblasts may undergo autophagy at bone fracture sites.…”
Section: Discussionsupporting
confidence: 51%
“…However, particulate LC3 fluorescence has not been observed in bone-lining cells or osteoblasts. Furthermore, autophagic osteocytes were primarily observed residing at a distance from the haversian canal2324. Our study found the expression of LC3 in osteoblasts which indicated that osteoblasts may undergo autophagy at bone fracture sites.…”
Section: Discussionsupporting
confidence: 51%
“…30 Autophagy was first shown to be a major survival mechanism of the long-lived osteocytes in stressful environments. 31,32,33 Recent work by Onal M. et al reports that autophagy suppression in osteocytes results in a reduced bone volume of 6-mo-old mice associated with an overall reduction in OB and OC numbers. 34 The study of Whitehouse et al, 35 then demonstrates that genetic truncation of the selective autophagic receptor Nbr1 in a murine model leads to increased osteoblast differentiation and activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…59 In fact, the expression of LC3 in osteocytes is greater than in osteoblasts. 61 Osteocytes are long-lived cells located in gaps delimited by mineralized bone matrix and, consequently, are positioned in an environment more susceptible to hypoxia and to the accumulation of oxidative stress. 55 It is believed that under these conditions autophagy plays an important role in the survival of osteocytes.…”
Section: Role Of Autophagy In Bone Biologymentioning
confidence: 99%
“…Non-functional mitochondria response to calcium-mediated stress, a hypoxia-inducing transcription factor (HIF-1) positively regulates autophagy, indicating that low oxygen tension serves as a regulator of autophagy in this type of cell. 61 Low-dose glucocorticoid treatment has also been shown to induce autophagy in osteocytes in response to increased oxidative stress caused by treatment, preserving the viability of these cells. [62][63][64] Studies indicate that autophagy also plays an important role in bone resorption by osteoclasts.…”
Section: Role Of Autophagy In Bone Biologymentioning
confidence: 99%